2017
DOI: 10.1103/physrevd.96.065027
|View full text |Cite
|
Sign up to set email alerts
|

Symmetries and conservation laws in non-Hermitian field theories

Abstract: Anti-Hermitian mass terms are considered, in addition to Hermitian ones, for PT -symmetric complexscalar and fermionic field theories. In both cases, the Lagrangian can be written in a manifestly symmetric form in terms of the PT -conjugate variables, allowing for an unambiguous definition of the equations of motion. After discussing the resulting constraints on the consistency of the variational procedure, we show that the invariance of a non-Hermitian Lagrangian under a continuous symmetry transformation doe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(119 citation statements)
references
References 21 publications
1
118
0
Order By: Relevance
“…There is a well known problem that seems to suggest that non-Hermitian quantum field theories are inconsistent, see e.g. [22,23,8]. However, just as for non-Hermitian quantum theories [24,25,26,27] there are methods and techniques to overcome these issues to obtain a perfectly consistent theory.…”
Section: Introductionmentioning
confidence: 99%
“…There is a well known problem that seems to suggest that non-Hermitian quantum field theories are inconsistent, see e.g. [22,23,8]. However, just as for non-Hermitian quantum theories [24,25,26,27] there are methods and techniques to overcome these issues to obtain a perfectly consistent theory.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that the free-field supersymmetric Dirac model is equivalent via a similarity transformation to a Hermitian supersymmetric model, but we have found that there is no such equivalence in the general Majorana case. As we have described in both models, there is an ambiguity in the definition of the supercurrent, and we have discussed the (non-)invariance of the Lagrangian and the (non-)conservation of the Noether current, which are analogous to the corresponding properties of PT -symmetric models with purely bosonic symmetries [20]. We have also extended the Dirac model to include Hermitian trilinear superpotential interactions, 5 in which case the model contains non-Hermitian trilinear bosonic interactions as well as non-Hermitian bilinear terms, whereas the dimension-4 interactions are Hermitian.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is, however, not unexpected, since we know that conserved currents are not related to transformations that leave the Lagrangian invariant in the case of non-Hermitian theories, see Ref. [20]. 2 We have seen already that there is a four-fold freedom in choosing the on-shell condition for the auxiliary fields F a .…”
Section: Supersymmetry Transformations and Supercurrentsmentioning
confidence: 94%
See 2 more Smart Citations